Deceased donors as nondirected donors in kidney paired donation. Issue 1 (19th September 2020) - Wang, Wen; Rees, Michael A.; Leichtman, Alan B.; Song, Peter X.‐K.; Bray, Mathieu; Ashby, Valarie B.; Shearon, Tempie; Whiteman, Andrew; Kalbfleisch, John D.
Abstract : As proof of concept, we simulate a revised kidney allocation system that includes deceased donor (DD) kidneys as chain‐initiating kidneys (DD‐CIK) in a kidney paired donation pool (KPDP), and estimate potential increases in number of transplants. We consider chains of length 2 in which the DD‐CIK gives to a candidate in the KPDP, and that candidate's incompatible donor donates to theDD waitlist. In simulations, we vary initial pool size, arrival rates of candidate/donor pairs and (living) nondirected donors (NDDs), and delay time from entry to the KPDP until a candidate is eligible to receive a DD‐CIK. Using data on candidate/donor pairs and NDDs from the Alliance for Paired Kidney Donation, and the actual DDs from the Scientific Registry of Transplant Recipients (SRTR) data, simulations extend over 2 years. With an initial pool of 400, respective candidate and NDD arrival rates of 2 per day and 3 per month, and delay times for access to DD‐CIK of 6 months or less, including DD‐CIKs increases the number of transplants by at least 447 over 2 years, and greatly reduces waiting times of KPDP candidates. Potential effects on waitlist candidates are discussed as are policy and ethical issues. Abstract : The authors suggest, after simulating allocation changes that would divert some deceased donor kidneys into kidney paired exchange programs, that transplant numbers can increase by several hundreds annually. See an editorial from Turgeon on page 5.